Epidemiology of Suicidal Behavior in Malaga (Spain): An Approach From the Prehospital Emergency Service - Moreno-Küstner, Berta; del Campo-Ávila, José; Ruíz-Ibáñez, Ana; Martínez-García, Ana I.; Castro-Zamudio, Serafina; Ramos-Jiménez, Gonzalo; Guzmán-Parra, José (Frontiers in Psychiatry, 2019)
Objective: This study aims to analyse the number and characteristics of calls made to the Málaga Prehospital Emergency Service (PES) for suicidal behavior based on sociodemographic, temporal, and health care variables. Method: This is a retrospective, descriptive study that records all calls made to the PES due to suicidal behavior (suicide attempts and completed suicides) in 2014. Sociodemographic variables (age, sex, and health district), variables related to the calls (time-slot, degree of sunlight, type of day, month, season of the year, prioritization, and number of resources mobilized) were extracted from these calls. The number of cases and percentages were presented for the qualitative variables. The rates per 100,000 were calculated by sex and health district and presented with the corresponding 95% confidence interval (CI). Results: Of the total valid calls to PES (n = 181,824), 1,728 calls were made due to suicidal behavior (0.9%). The mean age was 43.21 (±18) years, 57.4% were women, and the rate was 112.1 per 100,000 inhabitants. The calls due to suicidal behavior were in the younger-middle age segment, in the time-slot between 16 and 23 h and during daylight hours, on bank holidays, in spring and summer in comparison with winter, and with a peak of calls in August. The majority of these calls were classified as undelayable emergencies and mobilized one health resource. Conclusions: Prehospital emergency services are the first contact to the sanitary services of persons or families with suicide attempts. This information should be a priority to offer a complete overview of the suicide behavior.